Lower Miocene Planktic Foraminifera From The Temburong Formation In Menumbok, Klias Peninsula, Sabah - Junaidi Asis; Sanudin Hj.Tahir; Baba Musta; Basir Jasin (2018)
Lower Miocene sedimentary rocks of the Temburong Formation exposed at Kg. Assam, Menumbok, Klias Peninsula were examined for planktic foraminifera analysis. Four shale samples were collected and processes were done based on the standard micropaleontological method. This assemblage allows two local biozones to be recognized, namely the Globigerinoides primordius Zone (N4 zone) and the second assemblage belongs to the Globoquadrina dehiscens-Globoquadrina praedehiscens Zone (N5 zone). This study also indicates that the shale unit of the Temburong Formation from Kg. Assam was deposited in a distal part of a deep-sea fan environment during upper Oligocene‒lower Miocene (upper Chattian‒Aquitanian).